2010
DOI: 10.3168/jds.2010-3274
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium bifidum BF-1 suppresses Helicobacter pylori-induced genes in human epithelial cells

Abstract: Helicobacter pylori infection alters gene expression in host cells. Specifically, inflammatory chemokines such as IL-8 are upregulated in the gastric mucosa during H. pylori infection. Although the mechanism by which H. pylori causes inflammation of the gastric mucosa is not yet understood, many studies have suggested that nuclear factor kappa B (NF-κB) plays a key regulatory role in host cells. We have shown that preincubation with Bifidobacterium bifidum strain BF-1, a probiotic strain known to improve H. py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…ifidobacteria are intensively exploited by the food industry due to the presumed health beneficial effects they exert on the human host (1)(2)(3)(4)(5). However, the molecular mechanisms underlying these proclaimed health-promoting activities are still largely unknown.…”
mentioning
confidence: 99%
“…ifidobacteria are intensively exploited by the food industry due to the presumed health beneficial effects they exert on the human host (1)(2)(3)(4)(5). However, the molecular mechanisms underlying these proclaimed health-promoting activities are still largely unknown.…”
mentioning
confidence: 99%
“…In these environments, bifidobacteria reach a particularly high relative abundance as part of the infant gut microbiota (3)(4)(5), and this early life prevalence supports their purported role as modulators of various metabolic and immune activities of their immature host (1). Various members of the genus Bifidobacterium have attracted substantial scientific and commercial interest due to various professed beneficial health effects that they exert on their human host (6)(7)(8)(9)(10). Currently, the genus Bifidobacterium includes 47 taxa, involving 38 species and 9 subspecies (2,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…2a, b). In previous reports, some probiotic strains such as lactobacilli, lactococci, and bifidobacteria were reported to prevent IL-8 production from gastric epithelial cells inoculated with H. pylori [2,17,29,30]. Kim et al reported that Lactococcus lactis strain SL3 reduced IL-8 levels in MKN45 and AGS cells cultured with H. pylori [30].…”
Section: Discussionmentioning
confidence: 96%